Sincerely Fake: Exploring User-Generated Political Fakes and Networked Publics. (October 2020) - Ferrari, Elisabetta
This article investigates user-generated political satire, focusing in particular on one genre: fake political accounts. Such fakes, created as social media profiles, satirize politicians or political organizations by impersonating them. Through interviews with a sample of Italian fake accounts creators, I explore how the fakes navigate their fakeness vis-à-vis the affordances of social network sites and their publics. First, I map how the publics of the fake accounts react to the satire along two axes: one referring to the public's understanding of the satire and the other to the uses that the public makes of the satire. Second, I show how fakeness is part of everyday interactions in networked publics. Third, I argue for fakeness as a playful, powerful, and sincere critique of the political and its pretense to authenticity. By focusing on fake political accounts, this article provides insights on the place of fakeness in online communication beyond the debate around "fake news."